Perbandingan Penambahan Bioaktivator EM-4 (Effective Microorganisme) Dan Mol (Microorganisme Local) Kulit Nanas (Anana Comosus L.Merr) Terhadap Waktu Terjadinya Kompos - Supianor Supianor; Juanda Juanda; Hardiono Hardiono (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
The Comparison Of Additional Bio-Activator EM-4 (Effective Microorganism) And Mol (Microorganisme Local) Pineapple (Ananas Comosus L.Merr) Skin To The Composting Time. Composting is the reform process (decomposition) and stabilization of organic materials by microorganism in controlled environment (controlled) and its final outcome of humus or compost. It can be speed up by addition other ingredients called the activator. Activator is material consisting of enzymes and microorganisms (bacterial culture) that can accelerate the composting process. This study aimed to determine the effect of additional bioactivator EM-4 (Effective Microorganism) and MOL (Microorganism Local) pineapple skin (Ananas comosus l.merr) skin to the composting time. They was administered on each treatment and observed for 24 day. The result of the compost with the addition bio-activator EM-4 took for 16 days and compost with the addition MOL pineapple skin took for 14 days. Based on the statistical analysis by One Way Analysis of Variance method with α = 0.05 was significant effect between the addition of bio-activator EM-4 and MOL pineapple skin to the compositing time with average composting time for 16 and 14 days. Further study can be conducted by potential materials as basic raw materials for MOL such as fruits (banana, sugar cane, jackfruit), animal and human urine, and food scraps.